Circumstances of emergence of new words in the language - Melkonyan, Luiza (Bulletin of Yerevan University B: Philology, 2024)
The article refers to different principles of separating new words: comparing the different views of new words in linguistics in the works of both Armenian and foreign (mainly Russian) linguists. Then the linguistic and extralinguistic factors of the emergence of neologisms were distinguished, as well as the trends aimed at improving the nomenclature system of the language, which contribute to the emergence of neologisms. An attempt has been made to distinguish the most characteristic and comprehensive definition of neologisms from many points of view, distinguishing between the terms neologism and neology (new structure), which are often not defined in the same way or are sometimes identified. The examined linguistic units - words - were united under the single term neologisms. Thus, various new phenomena operating in the language are the basis for the creation of neologisms, such as: Giving new qualities to old words. New means of word formation. Creation of new words with existing lexical patterns. The tendency of economy of language unit. The tendency to generalize, regulate (the desire to give a common name to similar phenomena, objects, concepts). As a counterbalance to the tendency to regularize, generalize, the tendency to differentiate (дифференциация), adjustment also works. Giving emotional expressiveness to already known phenomena.